Numerical and experimental study of the thermal degradation process during the atmospheric re-entry of a TiAl6V4 tank. (May 2016) - Prévereaud, Y.; Vérant, J.-L.; Balat-Pichelin, M.; Moschetta, J.-M.
Abstract: To answer the question of space debris survivability during atmospheric entry ONERA uses its software named MUSIC/FAST. So, the first part of this paper is dedicated to the presentation of the ONERA tool and its validation by comparison with flight data and CFD computations. However, the influence of oxidation on the thermal degradation process and material properties in atmospheric entry conditions is still unknown. A second step is then devoted to the presentation of an experimental campaign investigating TA6V oxidation in atmospheric entry conditions, as the most of the debris found on ground are made of this material. Experiments have been realized using the MESOX facility implemented at the 6 kW solar furnace in PROMES-CNRS laboratory. Finally, an application of MUSIC/FAST is proposed on the atmospheric re-entry of a generic TA6V tank. Aiming at degradation assessment, a sensitive study to initial conditions is conducted. To complete computational analysis regarding degradation process by melting, a numerical analysis of the influence of oxidation on the thermal wall degradation during the tank atmospheric re-entry is presented as well. Abstract : Highlights: Description of MUSIC/FAST tool for atmospheric re-entry of space debris simulation. Simulations of the atmospheric re-entry of a TA6V tank with MUSIC/FAST. Experimental investigation of TA6V oxidation in atmospheric re-entry conditions.